Knowledge, expertise and policy in the examinations crisis in England - Ozga, J; Baird, J-A; Saville, L; Arnott, M; Hell, N (Routledge, 2023)
The Covid-19 pandemic suspended established practices that, in normal times, are seen as central to the functioning of education systems. For example, in England, school closures led to the cancellation of national examinations in 2020, and their attempted replacement with an algorithmic model. Following public outcry about what were seen as the unjust effects of the application of that model, there was a very public policy reversal, and examination grades were awarded on the basis of moderated teacher assessments or Centre Assessed Grades, resulting in substantial grade inflation. This paper draws on research that investigated the actors involved in examinations policy in this period and focuses especially on the sources of expertise and the kinds of knowledge that were mobilised - or not - in the decision to cancel examinations, to develop the algorithm and to revert to Centre Assessed Grades.